PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KINERJA APARATUR SIPIL NEGARA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PEKANBARU - Dehotman, Khornelis (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The study was conducted at the libraries and archives of Pekanbaru city. In analyzing data using descriptive and quantitative method. Descriptive is the methods associated with the collection and presentation of a data cluster so as to provide useful information. Y = 23,534 + 0,995X. From the results of the data can be explained as follows: The constant of 23,534 means that if training (X), 0, then the performance of employees (Y) has a value of 23,534. Regression coefficient Variable diklat (X) equal to 0,995, meaning if training (X) have increase 1 unit, hence employee performance will experience increase equal to 0,995 unit. The value of tcount is 5,171 bigger than ttable 2,000 with 0.000 significance level. This means that the training has a significant effect on employee performance. This means education and training (DIKLAT) have a significant effect on employee performance. Then H0 rejected H1 accepted, meaning that the incentive partially and significant effect on employee performance. Obtained r-square value (coefficient of determination) can be seen that R 0,598. This means that the training variables (X) have a close relationship to employee performance. While the value of R square of 0.358, this means the variables training (X) contributed to the influence of employee performance of 35.8% and the remaining 64.2% influenced by other variables not examined in this study